2016
DOI: 10.5433/1679-0359.2016v37n5supl2p3561
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological status of bovine tuberculosis in the Federal District of Brazil

Abstract: Considering the implementation of the National Program for the Control and Eradication of Animal Brucellosis and Tuberculosis (PNCEBT) in 2001, and the need to determine the epidemiological status of animal tuberculosis for future evaluation of the effectiveness of the measures laid down, the objective of this study was to estimate the prevalence and identify risk factors of bovine tuberculosis in the Federal District (DF) of Brazil, as well as to provide an input for the strategic management of PNCEBT. Field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 14 publications
1
21
0
6
Order By: Relevance
“…The prevalence of herds infected with bovine tuberculosis in Rio Grande do Sul was estimated to be 2.8% [1.8 -4.0] (Table 2), statistically equal to the states of Bahia, Pernambuco, Paraná, Mato Grosso do Sul, Mato Grosso, Rondônia, Goiás, and the Federal District, lower than those of the states of Espírito Santo, Minas Gerais, and São Paulo, and only higher than that of the state of Santa Catarina (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016). Although in Rio Grande do Sul differences were observed only between the regions with higher and lower prevalence of infected herds (Table 2), the values indicate a higher concentration of infected herds in regions 4, 5, and 6, located in the north of the state, in which dairy and mixed farms dominate (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of herds infected with bovine tuberculosis in Rio Grande do Sul was estimated to be 2.8% [1.8 -4.0] (Table 2), statistically equal to the states of Bahia, Pernambuco, Paraná, Mato Grosso do Sul, Mato Grosso, Rondônia, Goiás, and the Federal District, lower than those of the states of Espírito Santo, Minas Gerais, and São Paulo, and only higher than that of the state of Santa Catarina (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016). Although in Rio Grande do Sul differences were observed only between the regions with higher and lower prevalence of infected herds (Table 2), the values indicate a higher concentration of infected herds in regions 4, 5, and 6, located in the north of the state, in which dairy and mixed farms dominate (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on bovine tuberculosis conducted in 12 Federal Units, which hold 69% of the Brazilian herd, showed a prevalence of infected herds between 0.36% and 9.0%, in the Federal District and São Paulo, respectively (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, recent studies carried out in 13 states, which hold 75% of the Brazilian cattle population, showed prevalence of infected herds with tuberculosis among 0.36% of the Federal District and 9.0% of São Paulo (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies carried out in 13 states of Brazil, that hold 75% of the Brazilian cattle population, showed prevalence of tuberculosis infected herds between 0.36%, in the Federal District, and 9.0%, in São Paulo (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016).…”
Section: Introductionmentioning
confidence: 99%